Weight Gain in Severe Acute Malnutrition Children after Discharge from CMC Children’s Hospital Larkana Followed-Up for Two Months: Weight Gain in Severe Acute Malnutrition Children - Mehak, .; Shaikh, Nazia Faraz; Baloch, Dilijan; Gemnani, Vijia Kumar; Ahmed, Shahzad; Jamaro, Saifullah (Pakistan Journal of Health Sciences, 2025)
Globally, 19 million children under five suffer from severe acute malnutrition, causing 400,000 deaths annually. Early detection is crucial for treatment and reducing consequences in community and healthcare settings. Objectives: To assess weight gain in severe acute malnutrition (SAM) children two months after discharge from Children's Hospital. Methods: A prospective cohort study was conducted on children with SAM, receiving treatment at the oral therapy program (OTP) clinic at Chandka Medical College, Children Hospital, Larkana. Through consecutive sampling, 99 children aged 6-60 months with SAM and good appetites during discharge were enrolled. Mothers were explained about OTP. Follow-ups were conducted every 15 days up to two months after discharge to assess weight gain. SPSS version 22.0 was used to analyze the data. Results: Analysis revealed that 58.6% were male, with a mean age of 16.4 ± 8.2 months, while 52.5% were below 12 months old, mostly in rural areas (58.6%), and (32.3%) had illiterate maternal education status. Mean body weight at discharge was 4100 ± 620 grams. By the end of 2 months, weight gain was noted among 91 (91.9%) children. Weight gain was “good” in 51.5% of children, moderate in 34.3%, and poor in 14.2%. The weight gain was significantly associated with younger age groups (p=0.0085), literate mothers (p=0.0071), and increased monthly income families (p= 0.0416). Conclusions: The study found a significant association between weight gain and SAM management. Clinical-based treatment is often only the first step; however, sociodemographic factors like age, maternal education, and family income are crucial for sustaining nutritional and medical recovery and reducing morbidity and mortality.